Przerzuty nowotworów litych do narządu wzroku Charakterystyka częstości występowania i lokalizacji ognisk pierwotnych - Królewska, Katarzyna; Palacz, Olgierd; Zajączek, Stanisław (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
The aim of this paper is, to characterize ocular metastases of solid extraocular tumors and analyze the frequency and localization of their primary sites, according to literature data of 1967- 2002 years. The most common source of this metastases are breast, lung and prostate cancers in adults and neuroblastoma in children. Practically used diagnostic ways of ocular metastases in many cases omit histopathology investigation and for this reason in some cases, particularly with coexistence of hereditary cancer predisposition, second primary tumors may be misdiagnosed, as the distant - time ocular metastases.